2006
DOI: 10.1242/jcs.03159
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal polarity is regulated by glycogen synthase kinase-3 (GSK-3β) independently of Akt/PKB serine phosphorylation

Abstract: An essential step during the development of hippocampal neurons is the polarised outgrowth of a single axon. Recently, it has been suggested that inhibition of glycogen synthase kinase-3β (GSK-3β) via Akt/PKB-dependent phosphorylation of Ser9, specifically at the tip of the presumptive axon, is required for selective axonal outgrowth. We now report that, by using neurons from double knock-in mice in which Ser9 and Ser21 of the two GSK-3β isoforms have been replaced by Ala, polarity develops independently of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 23 publications
6
87
0
Order By: Relevance
“…In parallel with PI3 kinase/PKC-mediated signaling, localized inhibition of GSK3␤ is also essential for polarized outgrowth of single axons from hippocampal (Shi et al, 2004;Jiang et al, 2005;Yoshimura et al, 2005;Gartner et al, 2006) and dorsal root ganglion (Zhou et al, 2004) neurons and for migration of astrocytes (EtienneManneville and Hall, 2003b). This localized GSK3␤ inhibition appears to be required for adenomatous polyposis coli-and kinesinmediated transport of PAR3 to the plus ends of rapidly growing microtubules (Shi et al, 2004;Zhou et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In parallel with PI3 kinase/PKC-mediated signaling, localized inhibition of GSK3␤ is also essential for polarized outgrowth of single axons from hippocampal (Shi et al, 2004;Jiang et al, 2005;Yoshimura et al, 2005;Gartner et al, 2006) and dorsal root ganglion (Zhou et al, 2004) neurons and for migration of astrocytes (EtienneManneville and Hall, 2003b). This localized GSK3␤ inhibition appears to be required for adenomatous polyposis coli-and kinesinmediated transport of PAR3 to the plus ends of rapidly growing microtubules (Shi et al, 2004;Zhou et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Using double knockin mice bearing single point mutations in GSK-3b S9A and GSK-3a S21A , Gartner et al reported no obvious deficits in neuronal morphogenesis in vivo, or in vitro (Gartner et al 2006). However, using inhibitors of GSK-3a/b such as lithium chloride or, more specifically, SB-415286, SB-216763, and AR-A014418, Gartner et al (2006) were able to replicate the multiple axon phenotype obtained by others (Jiang et al 2005;Garrido et al 2007).…”
Section: Gsk-3 and Axon Specificationmentioning
confidence: 99%
“…Using double knockin mice bearing single point mutations in GSK-3b S9A and GSK-3a S21A , Gartner et al reported no obvious deficits in neuronal morphogenesis in vivo, or in vitro (Gartner et al 2006). However, using inhibitors of GSK-3a/b such as lithium chloride or, more specifically, SB-415286, SB-216763, and AR-A014418, Gartner et al (2006) were able to replicate the multiple axon phenotype obtained by others (Jiang et al 2005;Garrido et al 2007). These results indicate that although the exact role of Ser9/Ser21 phosphorylation in GSK-3 inactivation remains to be understood, or may involve an alternate site (Thornton et al 2008), it is clear that the catalytic activity of GSK-3 is a critical regulator of neuronal polarity in these in vitro paradigms.…”
Section: Gsk-3 and Axon Specificationmentioning
confidence: 99%
“…Localization, overexpression, and loss of function studies showed that spatially localized intracellular signals of a number of molecules, such as phosphoinositide-3-kinase (PI 3-kinase) 2 (9), phosphatidylinositol (3,4,5) triphosphate (10), Akt (11), glycogen synthase kinase-3␤ (11)(12)(13), collapsin response mediator protein-2 (CRMP-2) (12,14), mPar3/mPar6/atypical protein kinase C complex (9,15), Cdc42 (15,16), Rap1B (16), STEF/Tiam1 (15,17), Rac (15), adenomatous polyposis coli (18), JNK (19), and DOCK7 (20) are involved in axon specification for neuronal polarity formation. As downstream events, these pathways are thought to regulate cytoskeletal networks of actin filaments (21) and microtubules (20,22).…”
mentioning
confidence: 99%